2019
DOI: 10.1007/s11192-019-03307-5
|View full text |Cite
|
Sign up to set email alerts
|

Detecting bursty terms in computer science research

Abstract: Research topics rise and fall in popularity over time, some more swiftly than others. The fastest rising topics are typically called bursts; for example "deep learning", "internet of things" and "big data". Being able to automatically detect and track bursty terms in the literature could give insight into how scientific thought evolves over time. In this paper, we take a trend detection algorithm from stock market analysis and apply it to over 30 years of computer science research abstracts, treating the preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…A surprising result of this work different from ours, was that clustering and classification were determined as a single topical cluster. Tattershall et al (2020) analyze computer science research through burst detection and found some results similar to ours, e.g., the rise of popularity of Social Networks and related terms between 2004 and 2014, the lowered interest in web 2.0 in recent years. In Bhattacharya (2019), an analysis of machine learning literature has been performed based on measures from social network analysis, VOSviewer and keywords from the web of science.…”
Section: Related Worksupporting
confidence: 75%
See 1 more Smart Citation
“…A surprising result of this work different from ours, was that clustering and classification were determined as a single topical cluster. Tattershall et al (2020) analyze computer science research through burst detection and found some results similar to ours, e.g., the rise of popularity of Social Networks and related terms between 2004 and 2014, the lowered interest in web 2.0 in recent years. In Bhattacharya (2019), an analysis of machine learning literature has been performed based on measures from social network analysis, VOSviewer and keywords from the web of science.…”
Section: Related Worksupporting
confidence: 75%
“…A field sometimes using this approach and related to our work is the one of burst detection, i.e., the detection of sudden increases or decreases of interest in a topic (Kleinberg 2002). As a more recent application Tattershall et al (2020) applies burst detection methods from stock market trend analysis to detect bursts in research topics based on normalized term frequencies. A disadvantage over our approach here is the termbased analysis, which requires additional manual work and does not give an overall summary.…”
Section: Related Workmentioning
confidence: 99%
“…The algorithm uses information about topics in the previous step of the analysis to identify periods during which there was an increased number of articles published on a certain topic. Prior research (e.g., Tattershall et al ., 2020) has developed various burst detection algorithms. Here, we base our analysis on Kleinberg's (2003) burst detection algorithm, which has been used in prior publications to successfully identify emerging topics in academic publications (e.g., Mane and Börner, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…In order to determine the ‘hot’ topics, our research uses burst detection algorithms to identify periods of increased presence of topics. While there are a number of different burst detection algorithms (see Tattershall et al ., 2020), one of the most popular is Kleinberg’s (2003) burst detection algorithm, as it is widely used to identify emerging topics from increases in their occurrence in a literature (e.g., Mane and Börner, 2004). To implement the burst detection algorithm, we used the Python library called burst_detection (Version 0.1.3).…”
Section: Methodsmentioning
confidence: 99%